Investigation of the Relationship between Social Support and the Level of Hopelessness in Diabetic Patients: Descriptive Research - Karakaş, Neşe; Büyükbayram, Zeliha; Aktura, Seher Çevik; Evren, Bahri; Sarıtaş, Seyhan Çıtlık (My University, 2023)
Study aimed to investigate the relationship between social support and the level of hopelessness in diabetic patients. The study was carried out as descriptive research in the internal medicine clinic and polyclinics of a state hospital located in the southeast of Turkey. The population of the research consisted of adult patients diagnosed with Diabetes Mellitus who were followed up in the internal medicine clinics of the said hospital. The sample of the research was composed of 252 patients through power analysis with 0.05 error, 0.95 confidence interval and 0.95 representative power of the universe. In the collection of the data, Personal Information Form developed by the researchers, Multidimensional Scale of Perceived Social Support, and Beck Hopelessness Scale were employed. In the analysis of the data, descriptive statistics, t-test in independent groups, One-Way ANOVA, Mann-Whitney U test, correlation and Cronbach’s alpha reliability analysis were used. In the study, the patients’ mean scores obtained from Multidimensional Scale of Perceived Social Support and Beck Hopelessness Scale were found to be 65.2±15 and 11.2±1.8, respectively. It was determined that the patients had high levels of perceived social support and moderate levels of hopelessness. In the study, a negative and significant relationship was found between the mean scores obtained from Multidimensional Scale of Perceived Social Support and Beck Hopelessness Scale. It was also determined that as the patients’ perceived social support levels increase, their levels of hopelessness decrease.
Keywords: Social Support; Diabetic Patient; Hopelessne